4.6k views
17 votes
Choose the correct simplification of the expression (2ab5)3. (1 point) Question 8 options: 1) 8ab15 2) 8a3b8 3) 5a3b15 4) 8a3b15

User Kszyrver
by
5.0k points

1 Answer

8 votes

Answer:

4).
8a^(3)b^(15)

Explanation:

The Given expression is that,


(2ab^(5))^(3)

On simplifying,


(2ab^(5))^(3) =
(2ab^(5) )(2ab^(5)) (2ab^(5))

=
(2^(3) ) * (ab^(5))^(3)

= (2×2×2) × (
ab^(5) ×
ab^(5) ×
ab^(5))

=
8a^(3)b^(15)

Thus, option 4 i.e.
8a^(3)b^(15) is the correct simplification of the given expression.

User Mikos
by
4.7k points